Identification of productive clusters in the blueberry cultivation (Vaccinium corymbosum) in central Chile - Mena, Carlos; Ormazábal, Yony; Cantillana, Juan Carlos; Roco, Lisandro (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The understanding of the productive characteristics and tendencies of fruit producer’s territorial concentration can be explained starting from the singularities of the territory, the production techniques or the market conditions. This article analyzes the formation of clusters of blueberry producers in the Maule region in central Chile, based on the productive characteristics of the crops that include the technological levels, the age of the plantations and the size of the farms. For this, a two-step cluster analysis was performed to obtain homogeneous groups or conglomerates. The results obtained were analyzed in the ArcGIS software, using the Ripley K function, to determine their spatial concentration and to relate the spatial location of the orchards belonging to each cluster and their geographical distribution. The analysis indicates the existence of four clusters in the region, differing preferably by the sizes of the farms. The predominant technological level between the clusters identified is the intermediate, followed by the advanced. The clusters tend to generate spatial and geographic concentrations related with communication facilities and agroecological conditions (climate, soil, relief features). Results founded can improve focus of public efforts and private investments in the productive activity of blueberry cultivation.